Fragment-Sized EthR Inhibitors Exhibit Exceptionally Strong Ethionamide Boosting Effect in Whole-Cell Mycobacterium tuberculosis Assays - Nikiforov, Petar O. (ACS Chem Biol, 2017)
[Image: see text] Small-molecule inhibitors of the mycobacterial transcriptional repressor EthR have previously been shown to act as boosters of the second-line antituberculosis drug ethionamide. Fragment-based drug discovery approaches have been used in the past to make highly potent EthR inhibitors with ethionamide boosting activity both in vitro and ex vivo. Herein, we report the development of fragment-sized EthR ligands with nanomolar minimum effective concentration values for boosting the ethionamide activity in Mycobacterium tuberculosis whole-cell assays.